An examination of an incentive system to maximize performance in an automobile manufacturing environment - Fourie, Dawie (Rhodes University, Faculty of Commerce, Investec Business School, 2009)
This investigation was undertaken to explore an incentive system to maximize performance in an automotive manufacturing environment. The unit under study was a motor manufacturing company in the Eastern Cape in South Africa. The approach to this investigation was to start with a quantitative analysis to identify if there was a relationship between the incentive reward and employee satisfaction. This was to be done by correlation analysis between the Job Descriptive Index (JDI) and the performance related incentive reward (PBR) of the abovementioned company. The data was then used to develop an interview guide, which was used in a focus group study, to evaluate the current incentive system as a motivator of performance. The analysis of the qualitative interview data was to be done through the use of thematic analysis. Using a percentage based estimation per production line, 150 workers were selected from the 2100 shop floor workers. The Job Descriptive Index (JDI) questionnaires were used to measure the satisfaction index of the workers. The performance data was gathered from the company's incentive statistics over the past year, 2004. All other related data was obtained though thematic analysis by the researcher, who was interested to get the insiders' view. From the emic perspective, more data could be obtained by the researcher by probing with follow-up questions. After both the quantitative and qualitative procedures were completed, the results of the study were found to be much the same as those described in the reviewed literature. The quantitative analysis did not prove a significant correlation between incentive reward and satisfaction; and employees were most satisfied with work, supervision and co-workers and less satisfied with pay and promotion. The qualitative procedure (thematic analysis) highlighted that the current reward system was not motivating performance, but rather demoralised employees, as it was used as a punitive measure to encourage work attendance. The current system also confirmed the error made by many organisations, where the organization purely concentrates on motivating employees with extrinsic rewards and little thought is given to intrinsic recognition.
Keywords: Daimlerchrysler -- South Africa -- Eastern Cape; Incentives in industry -- South Africa -- Eastern Cape; Automobile industry and trade -- South Africa -- Eastern Cape; Automobile industry workers -- South Africa -- Eastern Cape -- Performance; Performance -- Management -- South Africa -- Eastern Cape -- Case studies; Employee motivation -- South Africa -- Eastern Cape -- Case studies; Goal setting in personnel management -- South Africa -- Eastern Cape -- Case studies; Achievement motivation -- South Africa -- Eastern Cape